INTERPRETASI AYAT-AYAT ALQURAN TENTANG FENOMENA CATCALLING - Roni, Muhammad (Jurnal Ushuluddin, 2024)
The phenomenon of catcalling, verbal harassment of women in public spaces, is increasingly becoming a significant social problem, including in Muslim-majority countries. The Qur'an provides ethical guidance regarding social interaction and respect for women. This article uses a thematic interpretation approach with a literature study method, examining Qur'anic verses that are relevant to this issue, especially regarding the ethics of maintaining views and maintaining women's dignity. The results of the study show that the Qur'an emphasizes the importance of maintaining politeness in social interactions, which can be the foundation in tackling catcalling. Islamic ethical concepts can shape a culture that is safer and respectful of women.